Reflections on Karl Kautsky and the Theory of Ultra-Imperialism: Social Democracy and International Relations - EMRE, YUNUS (Uluslararasi Iliskiler Konseyi Dernegi, Sogutozu Cad No 43, Tobb-Etu Binasi, Oda No 364, Sogutozu, Ankara 06560, Turkey, 2013)
This paper examines the ultra-imperialism theory of German politician and theorist Karl Kautsky. Karl Kautsky's ultra-imperialism conception is an essential approach which had significant influences on political history and International Relations. The article is divided into three parts. In the first part, the ultra-imperialism theory will be discussed after a brief examination of Karl Kautsky's basic assumptions and his importance in the history of social democracy. In the second part, the place of ultra-imperialism theory within the Marxist imperialism theories will be scrutinized. Third part is about the explanatory capacity of ultra-imperialism theory for post-Second World War international relations and its usefulness with regard to International Relations theories. The basic conclusion reached was that Karl Kautsky's ultra-imperialism theory has a significant analytical capacity for contemporary International Relations studies.
Keywords: Karl Kautsky; Ultra-Imperialism; Lenin; empire; imperialism; ultra emperyalizm; imparatorluk; emperyalizm